2021
DOI: 10.1371/journal.pone.0252038
|View full text |Cite
|
Sign up to set email alerts
|

Non-Indigenous Canadians’ and Americans’ moral expectations of Indigenous peoples in light of the negative impacts of the Indian Residential Schools

Abstract: The historical trauma associated with the Indian Residential School (IRS) system was recently brought to the awareness of the Canadian public. Two studies investigated how the salience of this collective victimization impacted non-Indigenous Canadians’ expectations that Indigenous peoples ought to derive psychological benefits (e.g., learned to appreciate life) and be morally obligated to help others. Study 1 found that modern racism was related to perceptions that Indigenous peoples psychologically benefitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…To this end, we adapted a paradigm established by Warner and Branscombe (2010, 2012). These authors consistently found that observers are more likely to ascribe higher moral obligations (to act rightfully towards others) to victims of injustices, because such convictions help them preserve their own just world beliefs (Warner & Branscombe, 2010, 2012; see also Doiron et al., 2021). Thus, in Study 5, we recycled the unfamiliar ethnic group context of Study 4, and we manipulated whether the agent's ethnic group was reported to have suffered in the past (moral obligations manipulation) or not (control condition).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we adapted a paradigm established by Warner and Branscombe (2010, 2012). These authors consistently found that observers are more likely to ascribe higher moral obligations (to act rightfully towards others) to victims of injustices, because such convictions help them preserve their own just world beliefs (Warner & Branscombe, 2010, 2012; see also Doiron et al., 2021). Thus, in Study 5, we recycled the unfamiliar ethnic group context of Study 4, and we manipulated whether the agent's ethnic group was reported to have suffered in the past (moral obligations manipulation) or not (control condition).…”
Section: Discussionmentioning
confidence: 99%
“…Euro-Caucasian settlers within Canada may deny or downplay the harms of colonialism and selectively focus on the 'positive benefits' [ 21 ], demonstrating an unwillingness to learn the true history of colonialism and its impacts on the health and social well-being of Indigenous Peoples. In this regard, the TRC final report [ 6 ] described how many non-Indigenous Canadians “hear about the problems faced by Indigenous communities, but they have almost no idea how these problems developed” (p.286).…”
Section: Educational Interventions Related To Indigenous Peoples and ...mentioning
confidence: 99%